2008
DOI: 10.1074/jbc.m707247200
|View full text |Cite
|
Sign up to set email alerts
|

Neph1, a Component of the Kidney Slit Diaphragm, Is Tyrosine-phosphorylated by the Src Family Tyrosine Kinase and Modulates Intracellular Signaling by Binding to Grb2

Abstract: There are several lines of evidence that the podocyte slit diaphragm (SD), which serves as a structural framework for the filtration barrier in kidney glomerulus, also plays an essential role as a signaling platform. Several SD components including nephrin and TRPC6 are known to be phosphorylated by a Src family tyrosine kinase (SFK), Fyn. Here we have characterized Neph1, another SD component, as a novel substrate of SFK. Fyn interacts with and phosphorylates the cytoplasmic domain of Neph1 in vitro and in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
90
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 50 publications
3
90
2
1
Order By: Relevance
“…Importantly, a comparative DLS analysis of these purified proteins stored in the same buffer at 4°C showed that although aggregation occurred in the tagless and GST-tagged proteins (at concentrations of ϳ1 mg/ml), His-Neph1-CD protein was remarkably more stable for longer durations. An earlier report also indicated that Neph1-CD protein was unstable in the solution and prone to aggregation (15). Overall, our results indicate that the His tag provides increased stability to Neph1-CD; however, the mechanism for this stability is uncertain.…”
Section: Volume 287 • Number 12 • March 16 2012mentioning
confidence: 52%
See 1 more Smart Citation
“…Importantly, a comparative DLS analysis of these purified proteins stored in the same buffer at 4°C showed that although aggregation occurred in the tagless and GST-tagged proteins (at concentrations of ϳ1 mg/ml), His-Neph1-CD protein was remarkably more stable for longer durations. An earlier report also indicated that Neph1-CD protein was unstable in the solution and prone to aggregation (15). Overall, our results indicate that the His tag provides increased stability to Neph1-CD; however, the mechanism for this stability is uncertain.…”
Section: Volume 287 • Number 12 • March 16 2012mentioning
confidence: 52%
“…Recent studies indicate that the interactions mediated by the PDZbinding domain of Neph1 are critical for Neph1 function (12). Currently, ZO-1 and Par proteins have been shown to interact with this domain, and our recent study demonstrates that Neph1 interacts with ZO-1 in a dynamic fashion that is regulated by Neph1 tyrosine phosphorylation (15,16). Further, Fyn-mediated tyrosine phosphorylation of Neph1 has been shown as a key signaling event that induces actin polymerization through recruitment of the adapter protein Grb2 (10).…”
Section: Complex Estimated Intensity Values From the Swaxs Data Andmentioning
confidence: 99%
“…In the rat model, PAN treatment has been shown to induce podocyte effacement, a characteristic of actin reorganization, and loss of podocyte function associated with proteinuria (12,18). More importantly, these changes in cultured podocytes and rat PAN model were associated with rapid tyrosine phosphorylation of Neph1 (10). Apart from PAN, the tyrosine phosphorylation of Neph1 was also noted in the ischemia reperfusion model of podocyte injury (12).…”
mentioning
confidence: 99%
“…This phosphorylation event that is primarily mediated by the phosphorylation of residues 637 and 638 in Neph1 was shown to recruit several proteins, including Grb2, Csk tyrosine kinase, and ZO-1 (10,12). Although the recruitment of Grb2 in cultured podocytes induced actin cytoskeleton reorganization at the cytoplasmic tail of Neph1 (6), the phosphorylation-dependent increased association between Neph1 and ZO-1 played a key role in defining the tight junction formation in podocytes (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation